Exploring the Role of Family Resilience in Predicting Marital Functioning: A Cross-Sectional Study - Arvin, Neda; Namjoo , Atefe; Mousavikhoo, Sayedeh Leila; Namjoo, Farhad; Keshavarz, Samira (Journal of Psychosociological Research in Family and Culture, 2024)
Objective: This study aimed to investigate the predictive relationship between family resilience and family functioning among married couples. It sought to understand how the construct of resilience within the family context influences the overall dynamics and health of marital relationships. Methods and Materials: Adopting a cross-sectional design, the study recruited 250 married individuals from counseling centers and social network groups. Participants were assessed using standardized measures of family resilience and family functioning. Linear regression analysis was employed to explore the predictive power of family resilience on family functioning, with preliminary checks for multicollinearity, normality, and homoscedasticity. Findings: The analysis revealed a significant predictive relationship between family resilience and family functioning. Specifically, higher levels of reported family resilience were associated with better family functioning scores. These findings were supported by statistical analyses, demonstrating that family resilience accounted for a substantial portion of the variance in family functioning. Conclusion: The study confirms the importance of family resilience as a significant predictor of family functioning in married couples. This underscores the potential for interventions aimed at enhancing family resilience to positively impact marital health and well-being. The findings advocate for the integration of resilience-building strategies in family therapy and counseling practices.